Anti-Corruption Training for Guardians of Students of Indonesian Migrant Workers in Malaysia - Dwiputri, Inayati Nuraini; Merlinda, Santi; Handayani, Sri; Pratama, Aditya; Zulfia, Binta (Pascasarjana Universitas Mataram, 2025)
To support the achievement of the quality of the nation's education through higher education, it should be in harmony and synergy with the activities of the Tri Dharma Lecturer. One of the program is international community service. This community service will be applied to the Indonesian worker community under the Indonesian Embassy, Malaysia. The demand for holistic education is increasingly urgent. The young generation, including Generation Alpha, must be equipped with knowledge, skills and strong values to face the increasingly complex challenges of the future. Anti-corruption education is an important aspect of the education process that is often overlooked or lacking in the formal curriculum. The Indonesian workers' community under the Indonesian Embassy in Malaysia is a gathering place for Indonesian families living abroad, with a focus on education and youth development. Parents have a crucial role in shaping their children's education. However, they often need the right guidance and resources to support their children's development in these aspects. Given these conditions, there is a need to maximize the role of parents in anti-corruption education for the Alpha Generation within the Indonesian working community under the Indonesian Embassy in Malaysia. By involving parents in the education process, we can create an environment that supports the full development of children's potential and help them become citizens of the country that have good responsibility and integrity.